2003
DOI: 10.1167/iovs.02-1332
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy with Brain-Derived Neurotrophic Factor As a Protection: Retinal Ganglion Cells in a Rat Glaucoma Model

Abstract: Overexpression of the BDNF gene protects RGC as estimated by axon counts in a rat glaucoma model, further supporting the potential feasibility of neurotrophic therapy as a complement to the lowering of IOP in the treatment of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(208 citation statements)
references
References 52 publications
8
196
0
4
Order By: Relevance
“…Since the exact molecular pathways of RGC death are not understood, several avenues of RGC neuroprotection are being investigated, including blocking glutamate excitotoxicity, stabilizing Ca 2+ homeostasis, inhibiting nitric oxide production, supplying neurotrophins, enhancing the stress protein response, preventing apoptosis, improving blood flow to the optic nerve and modulating immunologic status by vaccination. [4][5][6][7][8][9][10] Oxidative stress has been implicated in a variety of neurodegenerative diseases such as Alzheimer's, Parkinson, Huntington's and amyotrophic lateral sclerosis. [11][12][13][14][15][16][17] Oxidative stress has also been proposed to be a common factor in RGC death during glaucomatous neurodegeneration and after optic nerve transection, tissue hypoxia, ischemia and axonal transport disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Since the exact molecular pathways of RGC death are not understood, several avenues of RGC neuroprotection are being investigated, including blocking glutamate excitotoxicity, stabilizing Ca 2+ homeostasis, inhibiting nitric oxide production, supplying neurotrophins, enhancing the stress protein response, preventing apoptosis, improving blood flow to the optic nerve and modulating immunologic status by vaccination. [4][5][6][7][8][9][10] Oxidative stress has been implicated in a variety of neurodegenerative diseases such as Alzheimer's, Parkinson, Huntington's and amyotrophic lateral sclerosis. [11][12][13][14][15][16][17] Oxidative stress has also been proposed to be a common factor in RGC death during glaucomatous neurodegeneration and after optic nerve transection, tissue hypoxia, ischemia and axonal transport disruption.…”
Section: Introductionmentioning
confidence: 99%
“…After 4 weeks of experimental glaucoma, eyes that received intravitreal AAV-BDNF lost 32% of their RGC, compared to the 52% loss of RGC observed in eyes that received either a control AAV without BDNF or intravitreal saline. 38 This corresponded to a 38% rescue of RGC by the AAV-BDNF virus, an effect that was highly statistically significant. Further work is underway to determine the duration of the protective effect, although other studies have shown that AAV can mediate transgene expression in RGC for at least one year.…”
Section: Glaucomamentioning
confidence: 93%
“…For example, AAV2 vectors delivering genes encoding antiangiogeneic proteins, neurotrophic factors, or proteins with retinal specific functions have shown promise for the rescue of retinal degeneration in various animal models. [29][30][31][32][33][34][35][36][37] Attempts to correct the factor IX deficiency of hemophilia B by delivery of an AAV2 vector encoding FIX to muscle, liver, and lung in different animal models resulted in sustained FIX expression lasting for the lifetime of the animal. [38][39][40][41][42][43][44][45] To date eight additional primate serotypes of AAV have been identified, [46][47][48][49][50][51][52] the majority of which have been isolated as contaminants of adenoviral cultures.…”
Section: Aav Serotypesmentioning
confidence: 99%